PENGARUH PROGRAM ADIWIYATA TERHADAP PENDIDIKAN KARAKTER PESERTA DIDIK DI MTs AL-HIKAM JATIREJO DIWEK JOMBANG - Ihyauddin, Bilhaq; Umam , Khoirul; Ridhwan, Burhanuddin (EL-Islam, 2023)
Abstract: Allah has sent down a word in Q.S Al-A'raf:56 which indicates the existence of the law of balance in nature that must be sought to preserve it. Now, environmental sustainability is beginning to be threatened due to the increasing number of humans. This will have consequences if it is not accompanied by reforestation and community indifference to the environment. Therefore, it is important for people to care about the environment so as not to feel the consequences of their actions. Based on this study, researchers took the following problem formulations: 1. How is the Adiwiyata Program at MTs Al-Hikam Jatirejo Diwek Jombang?, 2. How is the Character Education of Students at MTs Al-Hikam Jatirejo Diwek Jombang?, 3. How does the Adiwiyata Program affect Student Character Education at MTs Al-Hikam Jatirejo Diwek Diwek Jombang?. To answer this question, this study used expost facto quantitative methods and questionnaires. The sample used was 46 Learners. The research data were analyzed using Statistical Package for the Social Sciences (SPSS) version 23. After a systematic study, it was found that there was a significant correlation between the Adiwiyata Program and Student Character Education based on SPSS calculations. Based on the analysis of studies conducted at MTs Al-Hikam Jatirejo Jombang, the value of t (8.836) is greater than the tabulation (2.015) and the level of significance (0.048) is smaller than 0.05. This led to the rejection of H0 and the acceptance of the Ha hypothesis, with some aspects of the madrasah in line with existing theories. Thus, this study concluded that there is a significant influence between the Adiwiyata Program and Student Character Education at MTs Al-Hikam Jatirejo Jombang.